Use of Xylazine in Drug-Facilitated Crimes - Jatupon Krongvorakul (2019)
© 2017 American Academy of Forensic Sciences Human xylazine poisoning is uncommon. This report describes the use of xylazine for intentional poisoning with criminal intent. Two incidents occurred within 3 weeks: the first involved one victim, and the second involved two victims. The clinical presentations were brief coma, bradycardia, hypotension, and hyperglycemia. The victims recalled having been given a drink from a stranger in a hospital waiting room before loss of consciousness. In the first case, general drug screening by gas chromatography/mass spectrometry (MS) revealed xylazine in the gastric contents, but liquid chromatography–tandem MS (LC-MS/MS) of serum did not. In the second incident, LC-MS/MS screening of both victims’ urine and serum samples revealed an unknown peak in the total ion chromatograms, which a molecular mass database identified as morantel or xylazine. The latter was confirmed by comparison with a xylazine standard. Based on this report, we suggest that xylazine should be classified as a controlled drug.